When truth commissions improve human rights - Olsen, T; Payne, L; Reiter, A; Wiebelhaus-Brahm, E (Oxford University Press, 2010)
Most studies of truth commissions assert their positive role in improving human rights. A first wave of research made these claims based on qualitative analysis of a single truth commission or a small number of cases. Thirty years of experience with truth commissions and dozens of examples allow cross-national statistical studies to assess these findings. Two recent studies undertake that project. Their findings, which are summarized in this article, challenge the prevailing view that truth commissions foster human rights, showing instead that commissions, when used alone, tend to have a negative impact on human rights. Truth commissions have a positive impact, however, when used in combination with trials and amnesties. This article extends the question of whether truth commissions improve human rights to how, when and why they succeed or fail in doing so. It presents a ‘justice balance’ explanation, whereby commissions, incapable of promoting stability and accountability on their own, contribute to human rights improvements when they complement and enhance amnesties and prosecutions. The article draws on experiences in Brazil, Chile, Nepal, South Korea and South Africa to illustrate the central argument.